Methotrexate inhibits BMP4 and abrogates the hypertrophic chondrocyte phenotype of synovial fibroblasts in juvenile idiopathic arthritis - Megan M. Simonds; Samuel T. Freer; Anne Marie C. Brescia (BMC, 2024)
Abstract Background Juvenile Idiopathic Arthritis (JIA) induces growth disturbances in affected joints. Fibroblast-like synoviocytes (FLS) play a crucial role in JIA pathogenesis. FLS overexpress bone morphogenetic protein 4 (BMP4) and have a chondrocyte-like phenotype. FLS contribute directly to joint growth disturbances through endochondral bone formation. We investigated the ability of methotrexate to inhibit BMP4 expression and alter the hypertrophic chondrocyte-like phenotype of JIA FLS. Methods We selected primary cells from three subjects with persistent oligoarticular JIA, three subjects who eventually extended to a polyarticular disease course, which we termed extended-to-be (ETB), and three subjects who had polyarticular arthritis at time of diagnosis. We treated cells with methotrexate and two BMP4 inhibitors: noggin and chordin. We measured protein concentration from three chondrocyte cell markers: collagen II, aggrecan, and collagen X as well as BMP4. Results ColX, marker of chondrocyte hypertrophy, was significantly increased in polyarticular FLS when compared to both persistent FLS and ETB FLS, making polyarticular FLS the most like hypertrophic chondrocytes. Methotrexate caused significant decreases in BMP4 and ColX expression in persistent, ETB, and polyarticular FLS when compared to respective untreated cells. Ligand-binding BMP4 antagonists, noggin and chordin, caused significant decreases in ColX expression in FLS from all three disease courses and significant increases in collagen II protein, an early chondrocyte marker, when compared to respective untreated cells. Conclusions Methotrexate, the first-line therapy in the treatment of JIA, mimics BMP4 antagonists by effectively lowering BMP4 and ColX expression in FLS. Inhibiting FLS from undergoing hypertrophy could prevent these cells from contributing to joint growth disturbances via endochondral bone formation.